Analogies in the social construction of the US-North Korean security dilemma - Er, Win Tan (College of Law, Government and International Studies, Universiti Utara Malaysia, 2010)
In most of the academic literature since the introduction of the security dilemma by John Herz and Herbert Butterfield in 1950-51, the concept has been dominated by neorealist scholars such as Robert Jervis, Ken Waltz, Charles Glaser and John Mearsheimer. Yet, with the end of the Cold War, a growing body of literature has chosen to approach the subject from perspective of constructivism, underlining how the notion of paradoxical security competition between defensively-minded states is itself a socially-constructed antagonistic relationship. Furthermore, critical constructivists have underlined the role of language in giving meaning to such antagonistic relationships in international politics. This paper seeks to build on the critical constructivist approach to analysing the security dilemma, and argues that the language of policymakers is crucial in giving meaning to interaction between states. Seen in this light, the author contends that discourse analysis of the US intervention in response to the North Korean invasion of South Korea in June 1950, in invoking the legacy of 1930s appeasement of Nazi Germany and how this failed to prevent the outbreak of the Second World War, is instructive in delineating the processes through which the Truman Administration came to identify North Korea as part of a monolithic communist bloc that had to be deterred, lest the pattern of events of the 1930s be replayed within the context of the Cold War.